Work flow improvement at Kenny Leather (M) Sdn. Bhd. - Norazmi, Mohamad Amirul Faiz; Abdul Razak Ramesh, Mohamad Iqbal Afham; Ahmad Jais, Mohamad Harizat; Ramli, Mohamad Najmi; Md Shah, Mohamad Sahril; Mohd Said, Mohamad Luqman Hakim; Mahmood, Salwa; Saleh, Aslinda (Penerbit UTHM, 2020)
Kenny Leather who was located at Merlimau Industrial Estate, Melaka driving force in the manufactures of leather. The company supply its product internationally and the product are well known globally due to their product’s quality and their commitment to give their best to the customer. Former world number one player of golf, Tiger Wood is among the user of hand glove that were made by this company. Kenny Leather has 200 workers and all of their workers are Malaysian. The managing director is Mr. Tadashi Fujisawa and main share partner is Kenny Co. Ltd. The company motto is ‘one for all and all for one’. Kenny Leather (M) Sdn Bhd is the factory processed all the material consists of leather. The nature of business is manufacturing leather gloves (for gloves), betting gloves, dress leather, cut leather and dyed sheep/goat skin leather. This factory is one of the biggest suppliers for leather material. In fact the former number one golfer in the world which is, Mr. Eldrick Tont Woods, known as Tiger Woods is using leather products made by the Kenny Leather. One company known as FootJoy which is the main company that sponsor Tiger Wood accessories for golfing is almost 80% was supplied by Kenny Leather.